Impact of CYP3A5 1* and 3* single nucleotide variants on tacrolimus pharmacokinetics and graft rejection risk in pediatric kidney transplant patients - Xajil-Ramos, Lesly Yanira; Gándara-Mireles, Jesús Alonso; Vargas Rosales, Rodrigo José; Sánchez García, Oscar Kevin; Ruano Toledo, Andrea Mariela; Aldana de la Cruz, Amy Kateleen; Lares-Asseff, Ismael; Patrón-Romero, Leslie; Almanza-Reyes, Horacio; Lou-Meda, Randall (Frontiers in Pharmacology, 2025)
Tacrolimus, a calcineurin inhibitor, is widely used to prevent allograft rejection in kidney transplant recipients. Its metabolism is predominantly mediated by the cytochrome P450 3A5 (CYP3A5) enzyme, and single nucleotide variants (SNVs) within intron 3 of the CYP3A5 gene are strongly associated with interindividual variability in enzyme expression and activity. These SNVs can generate a cryptic splice site, resulting in either preserved enzymatic function classified as expressers (CYP3A5 *1/*1 and *1/*3) or loss of function, classified as non-expressers (CYP3A5 *3/*3). Differential expression of CYP3A5 contributes to variability in tacrolimus pharmacokinetics and clinical outcomes, including graft rejection and therapeutic efficacy. In this study, we evaluated three pharmacokinetic parameters: trough concentration (TAC-C0), weight-adjusted daily dose (TAC-D, mg/kg), and dose-normalized trough concentration (TAC-C0/D). One-way ANOVA was used to assess differences in these parameters between CYP3A5 expressers and non-expressers. Additionally, Poisson regression was performed to examine associations between clinical/genetic variables and the incidence rate of acute rejection events. Genotyping was conducted in 45 pediatric kidney transplant recipients. The CYP3A5 *3/*3 genotype was most prevalent (66.7%), followed by *1/*3 (26.7%) and *1/*1 (6.7%). During the 6-month post-transplant period, CYP3A5 expressers required significantly higher tacrolimus doses to achieve target trough levels. Increased drug exposure was associated with a higher incidence of rejection events, whereas CYP3A5 expression correlated with a reduced rate of rejection. These findings underscore the clinical utility of CYP3A5 genotyping for optimizing tacrolimus dosing strategies. Carriers of functional CYP3A5 alleles (*1/*3 or *1/*1) benefit from individualized dose adjustments to achieve therapeutic concentrations and reduce the risk of graft rejection.